Wave characteristics of magnetic Pi 2 pulsations : Ground-magnetosphere correlations - Kuwashima, Masayuki (1983)
P(論文) The Pi2 wave characteristics are studied by using ULF data simultaneously obtained at the geosynchronous satellite, ATS 6,and at the conjugate ground-based stations; Syowa Station in Antarctica and Reykjavik in Iceland. It is experimentally clarified that the major axis of the Pi2 wave polarization rotates through 90°in a propagation from the magnetosphere to the ground through the ionosphere. departmental bulletin paper